Excessive day time sleepiness, poor sleep quality, and their association to caffeine consumption among young Informational Technology professionals - Raju, Aruna; Chandran, Madhavan; Fredrick, Jean (Industrial psychiatry journal, 2025)
Background: Sleep is essential for promoting physical and mental wellbeing. Short sleep duration and poor sleep quality are becoming more common among Informational Technology (IT) professionals; many IT workers seem to be using caffeine as a coping mechanism to alleviate the negative effects of insufficient sleep. Caffeine reduces sleep quality, prolongs sleep latency, and shortens sleep duration. Information on the sleep quality of young IT professionals is required to determine whether there may be a link between sleep quality, excessive daytime sleep, and caffeine usage. Aim: This cross-sectional study examined sleep quality in IT professionals and the associations between sleep quality, excessive daytime sleep, and caffeine consumption. Materials and Methods: Caffeine Consumption, Epworth Sleepiness Scale, and Pittsburgh Sleep Quality Index questionnaires were administered to 200 IT professionals aged 23-40 years via the online survey. Results: The average daily caffeine intake was 156.2 (98.7-252.5) mg per day, with coffee and tea being the primary contributor. A high prevalence of poor sleep quality (70%) was observed in the study population. Daily caffeine consumption was associated with poor sleep quality (r = 0.510, P > 0.01), and excessive day time sleep was associated with increased caffeine consumption (r = 0.363, P > 0.01). Excessive caffeine intake tends to be a predictive factor of poor sleep quality with an odd's ratio of OR 3.15, CI 2.34-4.25), P < 0.01. Conclusion: These findings reveal that poor sleep quality is prevalent among IT professionals. More research is required to determine the methods to improve sleep issues. Additionally, health education should be provided regarding the quantity of caffeine in products to avoid excess caffeine consumption and to improve sleep quality.